Impact of the COVID-19 pandemic on physical activity, smoking, alcohol use, and mental well-being-A longitudinal study of nursing students at Wroclaw Medical University in Poland - Aureliusz Andrzej Kosendiak; Michał Wysocki; Paweł Krysiński; Zofia Kuźnik; Bartosz Adamczak (Frontiers Media S.A., 2023)
IntroductionFrom the moment the first cases of coronavirus disease were detected in December 2019 until the announcement and duration of the pandemic, it was a negative experience for people around the world in various spheres of life. In connection with it, there have been many changes in our daily lives related to lifestyle, physical activity, or the mental sphere. The aim of the following paper is to determine the correlation between the COVID-19 pandemic and alcohol drinking, smoking, physical exercise, and lifestyle among nursing students in Poland.MethodsThe study was conducted among nursing students at Wroclaw Medical University before and during the COVID-19 pandemic. The survey consisted of completing the same anonymous online questionnaires five times by the same research group. The majority of respondents were women in the age between 18 and 30 years old and the significance level of data analysis was set at p < 0.05.Results and discussionIn October 2020, we recorded a large number of respondents experiencing anxiety/fear or being more stressed. Between the measurements, the highest average level of alcohol addiction (p < 0.001) was in October 2021 (8.71). Moreover, the percentage of respondents who felt as before increased (p = 0.021). As the pandemic continued, there was a systematic decline in the physical activity level (p < 0.001). In conclusion, the COVID-19 pandemic had a serious impact on the daily lives of the students.